2009
DOI: 10.1021/ma902122u
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity, Heat Capacity, and Cross-Linking of Polyisoprene/Single-Wall Carbon Nanotube Composites under High Pressure

Abstract: Polyisoprene (PI)/single-wall carbon nanotube (SWCNT) composites and pure PI have been cross-linked by high-pressure treatment to yield densified elastomeric states. Simultaneously, the SWCNT and cross-linked-induced changes of the thermal conductivity, heat capacity per unit volume, and glass transition were investigated by in situ measurements. The thermal conductivity of both the elastomeric and liquid PI improves ∼120% by the addition of 5 wt % SWCNT filler. The SWCNT filler (5 wt %) increases the glass-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 31 publications
4
55
0
Order By: Relevance
“…70 Only a few papers have reported measuring the heat capacity change in amorphous polymer-nanotube composites, with one very detailed study recently published by the author's research group. 59 As Figure 5 shows, a decrease of about 20% in the heat capacity change was found at low nanotube levels for polystyrene ($1 wt %) in agreement with studies on polycarbonate, 67,71 polymethyl methacrylate, 72 polyurethanes 73 and polyisoprene, 74 but was much smaller than a factor of three decrease found in an epoxy composite. 44 Our group's work was unique in that samples out to very high nanotube contents were examined.…”
Section: Dynamics: Glass Transition and Diffusion Coefficientsupporting
confidence: 85%
“…70 Only a few papers have reported measuring the heat capacity change in amorphous polymer-nanotube composites, with one very detailed study recently published by the author's research group. 59 As Figure 5 shows, a decrease of about 20% in the heat capacity change was found at low nanotube levels for polystyrene ($1 wt %) in agreement with studies on polycarbonate, 67,71 polymethyl methacrylate, 72 polyurethanes 73 and polyisoprene, 74 but was much smaller than a factor of three decrease found in an epoxy composite. 44 Our group's work was unique in that samples out to very high nanotube contents were examined.…”
Section: Dynamics: Glass Transition and Diffusion Coefficientsupporting
confidence: 85%
“…a decrease of 10%. Since this is significantly larger than 0.2% calculated by the mixture rule [6,12], it means that the MWCNTs decreases the heat capacity of nylon-6. Moreover, since the relative decrease is about the same above T g as that below (figure 2c), the MWCNT-nylon-6 interaction apparently reduces the vibrational and configurational heat capacities of nylon-6 to about the same extent, and this effect should make the nylon-6 matrix slightly more rigid.…”
Section: Resultsmentioning
confidence: 74%
“…Thus, adding relatively small amount of CNTs may dramatically improve κ of poor thermal conductors such as polymers. Tonpheng et al [6] reported an increase of κ by 120% for polyisoprene with 5wt% SWCNTs. The improvement was roughly proportional to the percentage of SWCNTs in the polymer composite, but the increase was lower than that predicted by simple mixture rules, which is likely due to high interfacial thermal resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity, which would affect the thermal strain rate and hence the cracking, is also not expected to vary significantly with the crosslink density. 27 Finally, the reaction may affect the film/substrate interfacial energy, although this cannot be ascertained at this stage.…”
Section: Discussionmentioning
confidence: 99%